POTENTIAL OF GENAI TECHNOLOGY IN DESIGNING PROGRAMMING ASSESSMENT CRITERI - Shekerbekova, Ш.Т.; Sagymbaeva, А.Е.; Zhaksylykov, А.Е.; Artykbaev, Н.Е.; Nagmetov, А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article discusses a system of level assignments for monitoring students' knowledge of programming, which is aimed not only at assessing theoretical knowledge, but also at testing practical skills, algorithmic thinking, and the effectiveness of software solutions. It also comprehensively analyzes the capabilities of GenAI (Generative Artificial Intelligence) technologies in developing assessment criteria. GenAI tools demonstrate efficiency in automatic code checking, logical structure analysis, test task generation, and assessment results analysis. In addition, it has been proven that the professional role of the teacher is important in determining the content of assessment, adapting proposals generated by GenAI, and making decisions that correspond to the level of development of the student. The article proposes criteria for assessing level assignments in programming, and substantiates modern methodological aspects and prospects for assessing programming knowledge using GenAI technologies.